CORRELATION OF INDICATORS OF THE STATE OF SUBJECTIVE WELL-BEING AND THE LEVEL OF DEVELOPMENT OF SELF-EDUCATION COMPETENCE - O. Sal'nikova; E. Bugaeva (Вестник Северо-Кавказского федерального университета, 2022)
The article describes and argues the tools of experimental work to identify the level of formation of self-education competence and the state of subjective well-being of students, presents the main diagnostic results; analyzes and interprets the results ofempirical research in the field of considering the interdependence of the level of formation of self-education competence and the state of subjective well-being. Conclusions about the interdependence of the processes of developing self-education competence and increasing the level of subjective well-being are presented. It is also concluded that it is necessary to take into account the correlation of the state ofsubjective well-being and the level of development ofself-education competence when building a psychological route for personal development and a pedagogical model of the educational process.